Air quality management systems in urban regions: The case of the emission trading programme reclaim in Los Angeles and its transferability to Vienna - Uwe Schubert; Andreas Zerlauth (European Regional Science Association (ERSA), 1998)
Clean air constitutes an essential element of the quality of living in urban regions. The discussion of how to manage air-quality in an era of shrinking public budgets and the trend towards deregulation has led to a rethinking of the present system in the urban region of Vienna. This paper is an attempt to contribute to these considerations by a comparative study of the "command&control" type of system operative in Austria (as regulated in the Austrian "Clean Air Act") and the new tradeable emission permit approach introduced in the urban region of Los Angeles (L.A.), California (the so called RECLAIM program) to reduce SOx and NOx emissions from stationary sources. The study utilized a survey of companies included in the respective pollution control programs in L.A. and Vienna, experts as well as administrators active in air quality management as a data base for the analysis. The survey is based on a mix of written responses to a questionnaire as well as personal interviews (conducted in 1996 and 97). Three main issues constituted the core of the analysis investigating the pros and cons of the approaches in practice: ? How much flexibility and discretionary latitude do the different policy systems grant the decision makers in the companies in the program to adopt the most efficient response to the request to reduce emissions? ? Which cost implications do the different systems have for the companies and the public management bodies? ? Which stimuli are provided in the long-run to innovate and promote emission reducing technical progress? Additionally the question was adressed which institutional changes were considered to have been the most troublesome in phasing out the old "command&control" type of system in L.A. and introducing the new RECLAIM program in 1994. Some basic propositions are developed how to introduce a tradeable permit system in the Vienna urban region. The results of the study do partly confirm some of the theses found in the theoretical literature, but offer additional insights on the institutional as well as political problems of intoducing a tradable emissions` permit scheme.
Keywords: 330